Mobile IP : - Perkins, Charles E (Addison-Wesley, 1998)
This book introduces the TCP/IP-savvy reader to the design and implementation of Internet protocols useful for maintaining network connections while moving from place to place. It describes the technology that makes mobile networking possible; in particular, it focuses on Mobile IP, the Internet Engineering Task Force (IETF) Standard for mobile networking. Written by Charles E. Perkins, a leader in the mobile networking field, this book discusses: mobile IP; route optimization; IP version 6; use of Dynamic Host Configuration Protocol (DHCP)...